2011
DOI: 10.1074/jbc.m111.230441
|View full text |Cite
|
Sign up to set email alerts
|

Association of ActA to Peptidoglycan Revealed by Cell Wall Proteomics of Intracellular Listeria monocytogenes

Abstract: Listeria monocytogenes is a Gram-positive intracellular bacterial pathogen that colonizes the cytosol of eukaryotic cells. Recent transcriptomic studies have revealed that intracellular L. monocytogenes alter expression of genes encoding envelope components. However, no comparative global analysis of this cell wall remodeling process is yet known at the protein level. Here, we used high resolution mass spectrometry to define the cell wall proteome of L. monocytogenes growing inside epithelial cells. When compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Thus, different active conformations of ActA might exist in vivo and play a role in deciding the fate of L. monocytogenes. An ActA-mediated lifestyle switch may also be driven by its binding to the peptidoglycan layer during the intracellular phase, although the signal(s) that enable such an association with the cell wall remain unknown (García-del Portillo et al, 2011). Interestingly, a decrease in ActA levels was also found to be correlated with the persistence of L. monocytogenes in vacuoles of non-phagocytic host cells (Kortebi et al, 2017).…”
Section: Dual States Of Prfa Regulates Lifestyles Of Listeria Monocytmentioning
confidence: 99%
“…Thus, different active conformations of ActA might exist in vivo and play a role in deciding the fate of L. monocytogenes. An ActA-mediated lifestyle switch may also be driven by its binding to the peptidoglycan layer during the intracellular phase, although the signal(s) that enable such an association with the cell wall remain unknown (García-del Portillo et al, 2011). Interestingly, a decrease in ActA levels was also found to be correlated with the persistence of L. monocytogenes in vacuoles of non-phagocytic host cells (Kortebi et al, 2017).…”
Section: Dual States Of Prfa Regulates Lifestyles Of Listeria Monocytmentioning
confidence: 99%
“…Mutants that lack sortase SrtA and SrtB activity show impaired LPXTG protein anchoring to the peptidoglycan [10] as well as differences in the relative levels of certain LPXTG proteins [11] . Recent studies also showed major changes in the cell wall proteome when L. monocytogenes proliferate inside epithelial cells [12] . Upregulation of defined LPXTG proteins has been observed in intracellular bacteria, including Internalin-A and Lmo0514 [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also showed major changes in the cell wall proteome when L. monocytogenes proliferate inside epithelial cells [12] . Upregulation of defined LPXTG proteins has been observed in intracellular bacteria, including Internalin-A and Lmo0514 [12] . The mechanisms that regulate the coordinated production of such a large number of LPXTG proteins nonetheless remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies, for instance using cryo-electron tomography, may elucidate the stressosome structure in vivo and further assess the contribution of membrane anchor proteins and RsbR paralogues in stressosome activation. Earlier MS-based proteomics studies characterised the Listeria proteome of both extraand intracellular bacteria in detail with a particular focus on the cell wall proteome containing many important virulence factors and proteins that interact with the host (Calvo et al, 2005;Garcia-del-Portillo et al, 2011;Quereda et al, 2013). Together, two decades of Listeria omics profiling by the Cossart laboratory and other groups resulted in more than 600 genome, transcriptome and proteome datasets that are integrated and available on listeriomics.pasteur.fr , an invaluable resource to decipher key regulatory mechanisms of Listeria gene expression by a systems biology approach.…”
mentioning
confidence: 99%